X-Type Tilted Quadrotor Flight Dynamic Modeling - Kuntjoro, W.; R. Abdullah, M.; E. M. Nasir, R.; Jaafar, J. (International Journal of Engineering and Technology, 2018)
Multirotor UAV such as quadrotor is ideal for photogrammetry application due to its hovering capability and flying at low altitude. It can be used for surveillance, photography, mapping, including Search and Rescue (SAR) operations. The flight of quadrotor requires that each motor produces the propulsion force against the gravitational force. Thrust differential approach is commonly used to control the movement of quadcopter (and also other type of multirotors). Control technique using thrust differential is not ideal to maintain platform attitude. The flight mission almost rely on additional stabilizer to carry a camera for capturing accurate images. Tilted rotor is an alternative control approach suitable for better platform flight attitude, which is horizontal flight. Flight dynamic behaviour of tilted rotor platform shall be understood. This paper shows an effort of development of the quadrotor flight dynamic mathematical model based on thrust differential and rotor tilted angle. X-type tilted configuration is used. Based on three dimensional kinetic analysis, the dynamic mathematical model were derived, and presented.Â